IMPROVING LISTENING SKILL USING LEARN ENGLISH BY LISTENING APPLICATION - Neri Permata Sari; Santi Susilowati; Odo Fadloeli (PROJECT (Professional Journal of English Education), 2019)
Listening is one of basic skill in English. Many of students feel difficult to learn listening especially in English. Using a multimedia as a teaching media is important in this process. It can catch students attention of the lesson. This research discusses improving listening skill using application “Learning English by Listening” as learning media for grade 10 Pharmancy SMK Kesehatan Fajar Kencana. This study is Classroom Action Research. This research uses several instruments such as test used for pretest and posttest and observation. This study involved 39 students as the respondent of the research. This study using Learn English By Listening application to improve students listening skill. Students scores in listening skill at the pretest and posttest were namely the mean score of pretest is 6.34 and the mean score of posttest was 6.97. In the last score it increased to 8.18. The students were very enthusiastic in this learning.